Della Walker (Mrs. Clinton Walker) residence exterior, Carmel (1950)
Exterior of house originally designed by Frank Lloyd Wright. The house sits on the Pacific Ocean, on top of large rocks that are on the beach. In the background, there is a small neighborhood overlooking the ocean. Two people are working on the roof as it is being renovated.